1999
DOI: 10.1002/(sici)1520-6777(1999)18:5<447::aid-nau6>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of trospium chloride after intravesical instillation in patients with neurogenic lower urinary tract dysfunction: A pilot study

Abstract: Oral drug treatment of detrusor overactivity often causes undesirable side effects in other organs. For some patients, in particular those with neurogenically induced detrusor overactivity (detrusor hyperreflexia), the tolerance level for adverse effects is low and oral treatment may become ineffective. Intravesical administration of the drug can diminish the side effects or increase treatment effectivity in patients who are (partially) refractory to oral treatment because the relative concentration of the dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Furthermore, intravesical instillation of oxybutynin (De Wachter and Wyndaele, 2003), tolterodine (Yokoyama et al, 2005), and darifenacin (Iijima et al, 2007) reduces distension-evoked activity of C-fiber afferents in rat bladder, an effect also seen after systemic administration of oxybutynin (De Laet et al, 2006). In patients with overactive bladder, intravesical administration of muscarinic antagonists, such as oxybutynin and trospium, is associated with reduced adverse affects (Madersbacher and Jilg, 1991;Fröhlich et al, 1998;Walter et al, 1999), whereas clinical efficacy remains (Enzelsberger et al, 1995;Fröhlich et al, 1998). Intravesical instillation of muscarinic antagonists may be a useful approach in neurogenic patients because these patients are already undertaking clean intermittent self-catheterization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, intravesical instillation of oxybutynin (De Wachter and Wyndaele, 2003), tolterodine (Yokoyama et al, 2005), and darifenacin (Iijima et al, 2007) reduces distension-evoked activity of C-fiber afferents in rat bladder, an effect also seen after systemic administration of oxybutynin (De Laet et al, 2006). In patients with overactive bladder, intravesical administration of muscarinic antagonists, such as oxybutynin and trospium, is associated with reduced adverse affects (Madersbacher and Jilg, 1991;Fröhlich et al, 1998;Walter et al, 1999), whereas clinical efficacy remains (Enzelsberger et al, 1995;Fröhlich et al, 1998). Intravesical instillation of muscarinic antagonists may be a useful approach in neurogenic patients because these patients are already undertaking clean intermittent self-catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials with some of the newer antagonists have demonstrated a beneficial effect on urgency (Freeman et al, 2003;Chapple et al, 2004;Zinner et al, 2004;Millard and Halaska, 2006;Wagg et al, 2006); this symptom is not attributable to activation of muscarinic receptors on the detrusor. Furthermore, the efficacy of intravesically applied antimuscarinic agents strengthens the case for a role for muscarinic receptors associated with the bladder mucosa (Madersbacher and Jilg, 1991;Enzelsberger et al, 1995;Fröhlich et al, 1998;Walter et al, 1999).…”
mentioning
confidence: 99%
“…Depending on physicochemical characteristics of instilled drug, studies demonstrate that only 1–7% of instilled dose reaches the systemic circulation after instillation 87, 88 . Instilled drugs also avoid the first pass effect of orally administered drugs 89 .…”
Section: Expert Opinionmentioning
confidence: 99%